2021
DOI: 10.20870/oeno-one.2021.55.2.4595
|View full text |Cite
|
Sign up to set email alerts
|

European grapevine moth in the Douro region: voltinism and climatic scenarios

Abstract: The European grapevine moth, Lobesia botrana (Lepidoptera: Tortricidae) is considered to be the main pest in the vineyards of the Douro Demarcated Region (DDR) due to the economic losses it can cause. Damage is caused by the larvae of this pest feeding on grape clusters, rendering them susceptible to Botrytis cinerea in mid-season and leading to the development of primary and secondary rot at harvest. Understanding this pest´s behaviour in the region under future climate scenarios is an increasing challenge. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
1
7
0
1
Order By: Relevance
“…The earliness of LB flights in this climate scenario is in line with other previous studies [2,23,57]. According to Reis et al [22], it was observed that LB phenology advances in the locations evaluated in the DDR. The earliness observed in the three flights in the 2021-2080 period was 7 to 12 days, under RCP4.5, and 15 to 24 days, under RCP8.5, when compared to the historic period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The earliness of LB flights in this climate scenario is in line with other previous studies [2,23,57]. According to Reis et al [22], it was observed that LB phenology advances in the locations evaluated in the DDR. The earliness observed in the three flights in the 2021-2080 period was 7 to 12 days, under RCP4.5, and 15 to 24 days, under RCP8.5, when compared to the historic period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019).…”
Section: Discussionsupporting
confidence: 91%
“…For our purpose, the combinations used (GCM-RCM chains) were CNRMALADIN, ICHECDMI, IPSLINERIS and MPICLM. More details can be found in Reis et al [22]. Daily T G , T N and T X were extracted from these climate model experiments.…”
Section: Climate Dataset For the Historic Period And Future Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…First, all of the suitable areas for Vitis vinifera are at risk of EGVM pest presence [10,11]. On the other hand, warming-derived phenological shifts imply a higher impact of first-generation EGVM and increased voltinism [12,13], increasing the land range EGVM's damaging effects. The first larval generation of the season usually attacks inflorescence, while later generations cause damage to the fruits.…”
Section: Introductionmentioning
confidence: 99%